Multi-Level Social Capital and Subjective Wellbeing Among the Elderly: Understanding the Effect of Family, Workplace, Community, and Society Social Capital - Xu, Zongyou; Zhang, Wenjie; Zhang, Xuewen; Wang, Yixi; Chen, Qing; Gao, Bo; Li, Ningxiu (Frontiers in Public Health, 2022)
Background Maintaining the subjective wellbeing of the elderly people is one of the major concerns in promoting health aging. This study concerned the influence of multi-level social capital on subjective welling and explored the affecting path among the elderly. Methods A total of 1,078 elderly individuals anonymously and effectively surveyed in 2018, data was collected including their family, workplace, community, society social capital and subjective wellbeing, we used the structural equation modeling to test the hypothesis relationships among the variables. Results We found that the total score of subjective wellbeing among the aging participants was 72.36 ± 10.08 on a range of 0–100. Family (β = 0.151, P < 0.001), workplace (β = 0.090, P < 0.001), community (β = 0.163, P < 0.001) social capital had a direct positive effect on subjective wellbeing. Society social capital had a direct positive effect on family (β = 0.253, P < 0.001), workplace (β = 0.585, P < 0.001), community (β = 0.438, P < 0.001) social capital. And society social capital had an indirect positive effect on subjective wellbeing through the mediating role of family, workplace, and community social capital. Conclusion The research demonstrated that all the micro, meso and macro levels of social capital have protective effects for subjective wellbeing through direct or indirect way, inspiring to provide continuous improvement measures for multi-level social capital aimed at the elderly people.